Inquiry-based learning to improve student engagement in a large first year topic. - Smallhorn, Masha; Young, Jeanne; Hunter, Narelle; Burke da Silva, Karen (Student Success v.6 n.2 p.65-71 https://doi.org/10.5204/ssj.v6i2.292, 2015)
Increasing the opportunity for students to be involved in inquiry-based activities can improve engagement with content and assist in the development of analysis and critical thinking skills. The science laboratory has traditionally been used as a platform to apply the content gained through the lecture series. These activities have exposed students to experiments which test the concepts taught but which often result in a predicted outcome. To improve the engagement and learning outcomes of Flinders University's large first year biology cohort, the laboratories were redeveloped. Superlabs were run with 100 students attending weekly sessions increasing the amount of contact time from previous years. Laboratories were redeveloped into guided-inquiry and educators facilitated teams of students to design and carry out an experiment. To analyse the impact of the redevelopment on student satisfaction and learning outcomes, students were surveyed and multiple choice exam data was compared before and after the redevelopment. Results suggest high levels of student satisfaction and a significant improvement in student learning outcomes. All disciplines should consider including inquiry-based activities as a methodology to improve student engagement and learning outcome as it fosters the development of independent learners. [Author abstract, ed]